Classroom Teachers' Perceptions of Difficult Children: A Phenomenological Study - Serap SARICELIK; Ahmet SABAN (Anı Publishing, 2021)
This study examined classroom teachers' perceptions of difficult children. It applied the descriptive phenomenology design of qualitative research approaches. In identifying the participants, the maximum variation sampling technique, one of the purposeful sampling methods, was used. Sixty classroom teachers working in Konya (20 from central schools, 20 from disadvantaged area schools, and 20 from private schools) have been selected and included in the study. Data were collected through semi-structured interviews and analyzed by the content analysis technique. Findings revealed that the participating classroom teachers were generally aware of difficult children's characteristics (such as having academic difficulties, exhibiting communication problems, inability to adapt socially, or disobeying classroom rules). According to the participants, there are at least five types of difficult children in schools: (1) children with giftedness or learning difficulties, (2) children who are overly active or silent, (3) children who are spoiled or not cared for by their families, (4) children who are excessively aggressive or quarrelsome, and (5) children who are distracted or uninterested. The study concludes that more research is needed to understand the difficult child phenomenon fully.